2013
DOI: 10.1016/j.nbd.2013.01.022
|View full text |Cite
|
Sign up to set email alerts
|

G9a-mediated histone methylation regulates ethanol-induced neurodegeneration in the neonatal mouse brain

Abstract: Rodent exposure to binge-like ethanol during postnatal day 7 (P7), which is comparable to the third trimester of human pregnancy, induces neuronal cell loss. However, the molecular mechanisms underlying these neuronal losses are still poorly understood. Here, we tested the possibility of histone methylation mediated by G9a (lysine dimethyltransferase) in regulating neuronal apoptosis in P7 mice exposed to ethanol. G9a protein expression, which is higher during embryogenesis and synaptogenic period compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
155
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(168 citation statements)
references
References 64 publications
(87 reference statements)
13
155
0
Order By: Relevance
“…The developing brain is so sensitive to ethanol exposure that even a single exposure can produce massive losses of neurons in several brain regions (Ikonomidou, et al, 2000) during the first few postnatal days in neonatal mice (postnatal days 4–10 [P4–10]), a developmental period which corresponds with the third trimester pregnancy in humans (Bayer, et al., 1993). Excessive acute ethanol intoxication in P7 mice prompts neurodegeneration in vital brain regions including the hippocampus and cortex (Ikonomidou, et al, 2000, Sadrian, et al, 2012, Subbanna, et al, 2014, Subbanna, et al., 2013a, Subbanna, et al, 2013b, Wilson, et al, 2011), as well as impairments in LTP (Izumi, et al, 2005, Sadrian, et al, 2012, Subbanna, et al, 2013a, Wilson, et al, 2011) and spatial memory task performance in adult mice (Subbanna, et al, 2013a). Similarly, the local and interregional brain circuitry of the olfacto-hippocampal pathway in adult mice is compromised when P7 mice are exposed to acute ethanol (Sadrian, et al, 2012, Wilson, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The developing brain is so sensitive to ethanol exposure that even a single exposure can produce massive losses of neurons in several brain regions (Ikonomidou, et al, 2000) during the first few postnatal days in neonatal mice (postnatal days 4–10 [P4–10]), a developmental period which corresponds with the third trimester pregnancy in humans (Bayer, et al., 1993). Excessive acute ethanol intoxication in P7 mice prompts neurodegeneration in vital brain regions including the hippocampus and cortex (Ikonomidou, et al, 2000, Sadrian, et al, 2012, Subbanna, et al, 2014, Subbanna, et al., 2013a, Subbanna, et al, 2013b, Wilson, et al, 2011), as well as impairments in LTP (Izumi, et al, 2005, Sadrian, et al, 2012, Subbanna, et al, 2013a, Wilson, et al, 2011) and spatial memory task performance in adult mice (Subbanna, et al, 2013a). Similarly, the local and interregional brain circuitry of the olfacto-hippocampal pathway in adult mice is compromised when P7 mice are exposed to acute ethanol (Sadrian, et al, 2012, Wilson, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence also shows that acute ethanol exposure alters dimethylation levels on lysines 9 and 27 of histone 3, which partially mediate ethanol's teratogenic effects in the brain [51] . The same research group also showed that ethanol exposure increases the levels of this mark in exon 1 of G9a, an HDM involved in alcoholinduced apoptosis [52] . Furthermore, epigenetic marks are emerging as major regulators of gene-by-environment interactions and have been implicated in the etiology of ethanol-induced neurodegeneration.…”
Section: Impact Of Alcohol On Histone Methylationmentioning
confidence: 86%
“…A key role of histone acetylation was observed in a recent study, in which the hyposensitivity to gamma-aminobutyric acid in the ventral tegmental area during alcohol withdrawal in mice was found to be mediated by HDAC [67] . Alcoholism is also suggested to be associated with neurodegeneration; indeed, in a recent study it was found that ethanol-induced acetylation of histone at G9a exon1 leads to neurodegeneration in neonatal mice [52] . Furthermore, in a study, histone acetylation was found to play a crucial role in regulating the transcriptional activity and contribute to the drug-induced alterations in gene expression and behavior.…”
Section: Impact Of Alcohol On Histone Acetylation/ Deacetylationmentioning
confidence: 99%
“…Ethanol exposure reduced the global expression levels of the HMTs G9a, Suv39 h1 and Setdb1, but not the activity of HATs or HDACs. Moreover, G9a-mediated H3K9me2 was shown to critically regulate ethanol-induced neurodegeneration and associated loss of cognition in rodents Subbanna et al, 2013). Consequently, inhibiting G9a before ethanol exposure at P7 prevented ethanol-induced deficits in LTP, memory and social cognition .…”
Section: Interference Of Histone Methylation and Addictionmentioning
confidence: 98%